Screen printed carbon electrode from coconut shell char for lead ions detection - Heliani, Kinkind Raras; Rahmawati, Fitria; Wijayanta, Agung Tri (International Journal of Renewable Energy Development, 2024)
This research aimed to produce a screen-printed carbon electrode (SPCE) from an activated coconut shell carbon. As a raw material, coconut shell char provides renewability and is abundantly available in the market. Meanwhile, SPCE offers a simple electroanalytical electrode because the working, counter, and reference electrodes are in one piece. The coconut shell carbon was activated by steam at 700 oC for 1h, producing AC700 that was then characterized to ensure the result by following per under carbon as the main component, the phases, crystal structure, surface area, morphology, and elemental content. The result showed that the surface area of AC700 is 816 m2/g, and the surface structure is porous, as identified by SEM images. Impedance analysis followed by data fitting and conductivity calculation found a high conductivity of 8.68 x 10-2 Scm‑1. The produced-SPCE or SPAC700 was modified by ferrocene at various compositions of 10%; 20%; and 30% of mass. The SPAC700-Fc30 provided the best performance for lead analysis with a detection limit of 0.35 mM, a quantitation limit of 1.17 mM, and good reproducibility with a Repeatability Coefficient (RC) of 0.022. SPAC700-Fc30 showed good lead ions detection despite under 10% Cu2+ and 10% Co2+ interferences. The result confirmed the potential use of coconut shell char as the raw material for SPCE production.